A Novel Approach of Position Estimation and Power Factor Corrector Converter Fed BLDC Motor - S. Kaliappan; R. Rajeswari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
This paper proposes a Power factor Corrected (PFC) Bridgeless Buck-Boost converter fed BLDC motor drive. The Bridgeless configuration eliminates the Diode Bridge Rectifier in order to reduce the number of components and the conduction loss. The position sensors used in BLDC drives have drawbacks of additional cost, mechanical alignment problems. These bottle necks results in sensorless technique. The Sensorless technique mostly relies on measurement of Back EMF to determine relative positions of stator and rotor for the correct coil energising sequence can be implemented. This paper introduces the offline Finite Element method for sensorless operation. The proposed sensorless scheme estimates the motor position at standstill and running condition. The obtained Power Factor is within the acceptable limits IEC 61000-3-2. The proposed drive is simulated in MATLAB/Simulink the obtained results are validated experimentally on a developed prototype of the drive.